2014
DOI: 10.1016/j.jval.2014.08.1282
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Adaptation of the Alcohol Quality of Life Scale for Use in Japan, China, and Korea

Abstract: Objectives: Alcohol consumption carries a risk of adverse personal, social, and health effects. Alcohol use disorder (AUD) is a problematic pattern of alcohol use leading to clinically significant impairment or distress. The aim of this study was to determine the patient-perceived impact of AUD. MethOds: Focus groups were conducted with a sample of patients with current or remitted AUD in the UK and France to identify key areas of impact from the patient perspective. The groups were audio-recorded and transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Health-related quality of life (HR-QoL) is acknowledged as critical domain to consider when assessing the effectiveness of treatment for AUDs and is often included as a secondary endpoint in clinical trials [7,8]. However, a 2012 systematic review of AUD studies using generic HR-QoL scales found that they were not well suited to showing treatment effects in subjects with AUD [9]. Thus, the Alcohol Quality of Life Scale (AQoLS) was developed as the first AUD-specific measure of HR-QoL for increased sensitivity in showing the effectiveness of therapeutic interventions from the patient's perspective [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health-related quality of life (HR-QoL) is acknowledged as critical domain to consider when assessing the effectiveness of treatment for AUDs and is often included as a secondary endpoint in clinical trials [7,8]. However, a 2012 systematic review of AUD studies using generic HR-QoL scales found that they were not well suited to showing treatment effects in subjects with AUD [9]. Thus, the Alcohol Quality of Life Scale (AQoLS) was developed as the first AUD-specific measure of HR-QoL for increased sensitivity in showing the effectiveness of therapeutic interventions from the patient's perspective [10].…”
Section: Introductionmentioning
confidence: 99%
“…The development process for the original scale also included a formal translatability assessment by translation experts to ensure the items were amenable to translation and cultural adaptation. The original English (UK) version of AQoLS was translated into Japanese, and formal cultural adaptation was completed in July 2013 [9]. We present here the first assessment of the psychometric properties of the Japanese version of the Alcohol Quality of Life Scale (AQoLS-Japan) in Japanese patients with an AUD.…”
Section: Introductionmentioning
confidence: 99%